Financial analysis for custom hire business of mechanical rice transplanter in Bangladesh - Sarkar, Surajit; Basir, Md Samiul; Ashik-E-Rabbani, Muhammad; Hossain, Md Mosharraf; Alam, Md Monjurul (Fundamental and Applied Agriculture, 2020)
This study was conducted to analyze the financial parameters of a mechanical rice transplanter operation for local service providers and entrepreneurs with hybrid rice variety. Two walking type mechanical rice transplanters of model Daedong DP 480 and DP 488 were used in the experiment. Field data from farmers and local service providers and also some necessary secondary data were used to establish the results of this research. The experiment was carried out in two different cropping seasons, Boro-2018 at Bangladesh Agricultural University, Mymensingh and in Aman-2018 at Mothbaria village of Dumuria Upazila, Khulna. Daedong DP 480 transplanter was used in Boro-2018 season and in Aman season, Daedong DP 488 transplanter was used. The effective field capacity was found 0.173 ha h−1 and 0.189 ha h−1 . for DP 480 and DP 488 transplanter, respectively. Considering 10% discount factor, the NPV of DP 480 transplanter was found 7358 USD with IRR of 59% and for DP 488, NPV was 8037.97 USD at 63% IRR. The NPV and IRR indicate the financial viability of rice transplanter entrepreneurship as the IRR is much higher than the bank interest rate. The payback period of DP 480 was found 1.60 years whereas the DP 488 will return the capital in 1.51 years. By analyzing the BCR of the two rice transplanters, use of transplanter was also found profitable for entrepreneurs for custom hire services as the BCR of DP 480 and DP 488 transplanters were found 1.62 and 1.66, respectively. The minimum tenure for the economic use of the transplanters was found 20.36 ha and 21.01 ha per year for DP 480 and DP 488 transplanter, respectively. Evaluating the financial parameters of total procedure of mechanical transplanting, the machine transplanting was found to be more economic over manual transplanting with both hybrid and inbred rice varieties when it is subjected to cover up more than 10.1 ha and 6.7 ha yr−1, respectively.